Structure of Silicon Wafers Planar Surface before and after Rapid Thermal Treatment - U. A. Pilipenko; A. A. Sergeichik; D. V. Shestovski; V. A. Solodukha (Приборы и методы измерений)
Presently it is important to remove mechanically disturbed layer on wafer surface during creation of up-to-date microelectronic products. Rapid thermal treatment with optical pulses of second duration is one of the applicable methods for removing disturbances in crystal lattice emerging after ion implantation. However the crystal structure of mechanically disturbed layer on wafer planar side is still unclear. Researches by transmission electronic method, analysis of diffraction reflection curve and electronic Auger spectroscopy has failed to provide reliable data about the state of crystal lattice in surface layer of at least 30 nm thickness. Hence it was impossible to suggest a model of solid phase recrystallization and to present its mathematical description. The goals of the work were as follows: – identify of silicon crystal lattice state in surface layer of 30 nm thickness before and after rapid thermal treatment by backward reflected electrons diffraction method using raw Si wafers surface; – analysis of contamination element composition on the surface of raw silicon before and after rapid thermal treatment; – model development for solid phase recrystallization of surface disturbed layer after rapid thermal treatment and its mathematical description. Images of back ward reflected electrons diffraction using surface layer of raw silicon wafers' of 30 nm thickness and also the results of the planar surface of raw silicon wafers' cleaning from impurities are provided. Processes reducing the activating energy of mechanically disturbed silicon layer recrystallization process were suggested and its mathematical description was provided. Parameters of rapid thermal treatment mitigating the thermal impact on silicon wafer for recrystallization of mechanically disturbed layer on its planar surface ware defined.